2020
DOI: 10.1021/acs.iecr.9b06600
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic Reduction of CO2 for Efficient Methanol Production: Au Nanoparticles as Electrocatalysts and Light Supports

Abstract: Conversion of CO2 into value-added fuels and chemicals faces the challenges of high overpotential, low selectivity for desired products, and sluggish multi-electron transfer kinetics. Plasmon-mediated electrocatalytic methods show potential for overcoming these problems. In this work, choosing Au nanoparticles (NPs) as the dual-functional material of the electrocatalyst and plasmonic support, methanol can be efficiently produced from CO2 reduction. The dependences of current density and Faradaic efficiency (FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
(127 reference statements)
0
19
0
Order By: Relevance
“…For example, Wang's group reported an Ag nanoparticle decorated p-Si nanowire array catalyst, [133] which could realize photoelectrocatalytic CO 2 reduction to syngas with the adjustable H 2 /CO molar ratio ranging from 1 to 4. The Ag nanoparticles with the size of 8.2 nm provide a balance between *CO formation and CO adsorption, which selectively produced CO prod- [135] Copyright 2020, American Chemical Society. c) EtOH yields of CuFeO 2 /Nb-TNTs photocathode with different coating amounts at −0.4 V under illumination.…”
Section: Co 2 To Comentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wang's group reported an Ag nanoparticle decorated p-Si nanowire array catalyst, [133] which could realize photoelectrocatalytic CO 2 reduction to syngas with the adjustable H 2 /CO molar ratio ranging from 1 to 4. The Ag nanoparticles with the size of 8.2 nm provide a balance between *CO formation and CO adsorption, which selectively produced CO prod- [135] Copyright 2020, American Chemical Society. c) EtOH yields of CuFeO 2 /Nb-TNTs photocathode with different coating amounts at −0.4 V under illumination.…”
Section: Co 2 To Comentioning
confidence: 99%
“…Plasmon‐mediated electrocatalysis has been regarded as a promising approach to realize highly active and selective CO 2 conversion into higher value‐added chemicals. For example, Lu et al found that the plasmonic Au was an ideal catalyst to generate abundant electrons with high photon energy, [ 135 ] which could be easily injected into CO 2 molecules and intermediates to activate the overall reaction system. Meanwhile, the generated photon flux would initiate C—C coupling toward high‐order product formation ( Figure 17 a ).…”
Section: Photoelectrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97] In detail, the generated electrons of the conduction bands can take part in the CO 2 reduction reaction, while the generated holes of the valence band usually get involved in some water oxidation. [98,99] Furthermore, the photocatalytic reduction of CO 2 has many kinds of catalytic products including CO, CH 3 OH, HCOOH, CH 4 , etc. due to its reaction may involve the catalytic process of 2-8 electrons (Equations ( 1)-( 7)).…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic transformation of CO 2 into value-added chemicals and fuels has been regarded as one of the most promising ways to realize the valorization of CO 2 [5]. In this context, several strategic options, including electrochemical [6][7][8][9][10][11][12], thermochemical [13][14][15], photocatalytic [16][17][18] and photoelectrochemical [19][20][21][22] approaches, have been developed to undertake the CO 2 conversion. Among them, the electrochemical reduction of CO 2 is regarded as the most prospective way, because it allows one to combine with carbon capture and storage technology, and to utilize renewable energy (such as solar energy and wind energy), as inputting energy and water as a reductant to reduce CO 2 into various carbon-based fuels and chemicals (e.g., CO, HCOOH, CH 4 , C 2 H 4, and CH 3 OH) in a modular electrochemical reactor under ambient temperature and pressure [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%